2014
DOI: 10.5713/ajas.2013.13481
|View full text |Cite
|
Sign up to set email alerts
|

Production of Mutated Porcine Embryos Using Zinc Finger Nucleases and a Reporter-based Cell Enrichment System

Abstract: To facilitate the construction of genetically-modified pigs, we produced cloned embryos derived from porcine fibroblasts transfected with a pair of engineered zinc finger nuclease (ZFN) plasmids to create targeted mutations and enriched using a reporter plasmid system. The reporter expresses RFP and eGFP simultaneously when ZFN-mediated site-specific mutations occur. Thus, double positive cells (RFP+/eGFP+) were selected and used for somatic cell nuclear transfer. Two types of reporter based enrichment systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Zinc (Zn) is an important trace element involved in forming more than 300 kinds of metalloenzymes that affect biochemical processes of the whole body. Known functions of Zn include: regulating immune response, improving gastrointestinal digestion and interacting with the nervous system [ 1 ]. Many studies demonstrated Zn deficiency is common in several psychiatric disorders including induction of Alzheimer’s disease [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc (Zn) is an important trace element involved in forming more than 300 kinds of metalloenzymes that affect biochemical processes of the whole body. Known functions of Zn include: regulating immune response, improving gastrointestinal digestion and interacting with the nervous system [ 1 ]. Many studies demonstrated Zn deficiency is common in several psychiatric disorders including induction of Alzheimer’s disease [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the “editing windows” of the Target-AID and BE systems are different, these two base-editing systems may be used complementarily for complex porcine genome engineering. Furthermore, in combination with zygote electroporation [ 31 ] or somatic cell nuclear transfer [ 32 ], it is expected that base-edited pigs can be generated using the Target-AID system. Particularly, for generating PERV inactivated pigs, ribonucleoprotein (RNP) based Target-AID is recommended to avoid safety issue in clinical xenotransplantation.…”
Section: Resultsmentioning
confidence: 99%
“…As the "editing windows" of the Target-AID and BE systems are different, these two base-editing systems may be used complementarily for complex porcine genome engineering. Furthermore, in combination with zygote electroporation [31] or somatic cell nuclear transfer [32], it is expected that base-edited pigs can be generated using the Target-AID system.…”
Section: Resultsmentioning
confidence: 99%